Diagnosis and treatment of destructive forms of acute pancreatitis - V. V. Mishchenko; V. V. Hrubnyk; P. I. Pustovoyt; V. V. Horyachyy; V. V. Velychko; R. Yu. Vododyuk (Сучасні медичні технології)
Purpose of the study. The study of the diagnosis and treatment of destructive forms of acute pancreatitis and the identification of possible ways to optimize them.